Has COVID-19 Induced Labor Market Mismatch? : Evidence from the US and the UK - Pizzinelli, Carlo (IMF Working Papers; Working Paper ;, 2022)
This paper studies whether labor market mismatch played an important role for labor market dynamics during the COVID-19 pandemic. We apply the framework of Sahin and others (2014) to the US and the UK to measure misallocation between job seekers and vacancies across sectors until the third quarter of 2021. We find that mismatch rose sharply at the onset of the pandemic but returned to previous levels within a few quarters. Consequently, the total loss in employment caused by the rise in mismatch was smaller during the COVID-19 pandemic than during the Global Financial Crisis. The results are robust to considering alternative definitions of job seekers and to using a measure of effective job seekers in each sector. Preliminary evidence suggests that increased inactivity among older workers, the so called She-cession (particularly in the US) and shifting worker preferences amid strong labor demand are more prominent explanations for the persistent employment shortfall vis-a-vis pre-COVID levels.